Medicine and evolution : current applications,future prospects. - Elton, Sarah; O'Higgins, Paul. (Boca Raton : CRC Press, 2008)
Thinking about disease from an evolutionary perspective might provide novel insights into causality and suggest different approaches to health and illness. Medicine and Evolution: Current Applications, Future Prospects highlights areas of research into the evolutionary basis of health and disease."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Human evolution; Evolution (Biology)